Mitochondria-cytoskeleton associations in mammalian cytokinesis. Issue 1 (March 2016) - Lawrence, E.; Boucher, E.; Mandato, C.
Abstract Background The role of the cytoskeleton in regulating mitochondrial distribution in dividing mammalian cells is poorly understood. We previously demonstrated that mitochondria are transported to the cleavage furrow during cytokinesis in a microtubule-dependent manner. However, the exact subset of spindle microtubules and molecular machinery involved remains unknown. Methods We employed quantitative imaging techniques and structured illumination microscopy to analyse the spatial and temporal relationship of mitochondria with microtubules and actin of the contractile ring during cytokinesis in HeLa cells. Results Superresolution microscopy revealed that mitochondria were associated with astral microtubules of the mitotic spindle in cytokinetic cells. Dominant-negative mutants of KIF5B, the heavy chain of kinesin-1 motor, and of Miro-1 disrupted mitochondrial transport to the furrow. Live imaging revealed that mitochondrial enrichment at the cell equator occurred simultaneously with the appearance of the contractile ring in cytokinesis. Inhibiting RhoA activity and contractile ring assembly with C3 transferase, caused mitochondrial mislocalisation during division. Conclusions Taken together, the data suggest a model in which mitochondria are transported by a microtubule-mediated mechanism involving equatorial astral microtubules, Miro-1, and KIF5B to the nascent actomyosin contractile ring in cytokinesis.